Using artificial intelligence in support of climate change adaptation Africa: potentials and risks - Walter Leal Filho; Gouvidé Jean Gbaguidi (Humanities & Social Sciences Communications)
Climate change poses significant threats to African countries, with increasing temperatures, erratic rainfall patterns, and extreme weather events impacting ecosystems, agriculture, water resources, and human livelihoods. Artificial intelligence (AI) may offer valuable support in climate change adaptation efforts in the field of agriculture. However, considerable constraints also need to be addressed to maximise AI’s effectiveness. Against this background, this article outlines the potentials and risks of deploying AI in agriculture, as well as the need for clear regulatory frameworks for AI deployment, establishing guidelines that promote innovation while addressing ethical and legal concerns.